Involvement of ROA, EPS, and DER to Stock Prices in listed coal mining sub-sector on IDX 2020-2024 - Madjid, Nurcholis; Dhevyanto, Benny (Al-Mashrof: Islamic Banking and Finance, 2025)
This study aims to examine the effect of Return on Assets (ROA), Earnings Per Share (EPS), and Debt to Equity Ratio (DER) on stock prices in coal mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. These financial ratios serve as important indicators for investors to evaluate a company performance and make informed investment decisions. The study adopts a quantitative descriptive method, using secondary data obtained from audited annual reports from Indonesia Stock Exchange.The results show that ROA does not have a significant impact on stock prices, and its negative coefficient suggests a potential mismatch between asset efficiency and investor expectations. EPS, on the other hand, has a positive and significant influence, indicating that higher earnings per share are positively associated with higher stock prices. DER shows a negative but statistically insignificant effect, suggesting that high leverage may be perceived as a risk but does not strongly influence investor behavior within this period. These findings imply that investors in the coal mining sector tend to prioritize profitability signals like EPS over traditional asset efficiency or capital structure ratios. The study provides valuable insights for investors seeking to reduce risk and maximize returns, and for companies aiming to enhance their financial appeal in capital markets. Keywords: ROA, EPS, DER, Stock Price